Theory and problems of advanced mathematics for engineers and scientists - Spiegel, Murray R. (New York: McGraw-Hill Book Company, 1983)
About the book This Schaum's Study Guide is the perfect way for scientists and engineers to master the tools of advanced mathematics for scientists and engineers. Fully stocked with solved problems?950 of them?it shows you how to solve problems that may not have been fully explained in class. Plus you get hundreds of additional problems to use for practice, with answers at the back of the book. Ideal for independent study, brushup before exams, or preparation for professional tests, this Schaums Guide is clear, complete, and well-organized. It's the perfect supplement for any course in advanced mathematics for science and engineering, and a super helper for the math-challenged. This Schaum?s Outline provides a comprehensive review of advanced mathematical theory and methods you?ll really use in high-tech industries and scientific research.
Index 399-407p.
Keywords: Mathematics for Engineers